New synthetic route to pyrimido[4, 5-g]quinazoline-4, 9-diones. Issue 17 (22nd April 2015) - Quinn, Jesse; Jin, Edward; Li, Yuning
Graphical abstract: Abstract: A facile and moderate to high yielding protocol is reported for the synthesis of 2, 7-bis(5-bromothiophen-2-yl)-3, 8-bis(2-decyltetradecyl)-3, 8-dihydropyrimido[4, 5- g ]quinazoline-4, 9-dione, which can be potentially used to synthesize other pyrimido[4, 5- g ]quinazoline-4, 9-diones. Moreover, new pyrimido[4, 5- g ]quinazoline-4, 9-diones synthesized by this route can potentially be used as organic semiconductors.